A review of the taxonomic history and biodiversity of the genus Urodeta (Lepidoptera: Elachistidae: Elachistinae), with description of new species - de Prins, Jurate; Sruoga, Virginijus (Zootaxa, 2012)
The taxonomic history of the genus Urodeta Stainton 1869 (Lepidoptera: Elachistidae: Elachistinae) is presented. Three new species: Urodeta acinacella Sruoga et De Prins, sp. nov., U. quadrifida Sruoga et De Prins, sp. nov. and U. trilobata Sruoga et De Prins, sp. nov., from South Africa are described. The new species are diagnosed and illustrated with photographs of the adults and genitalia. A global, annotated catalogue of the Urodeta species diversity is presented. The impact of formerly published taxonomic decisions on the position of Urodeta within Gelechioidea is discussed.